An early HMGB1 rise 12 hours before creatinine predicts acute kidney injury and multiple organ failure in a smoke inhalation and burn swine model - Yang, Zhangsheng; Cancio, Tomas S.; Willis, Robert P.; Young, Matthew D.; Kneifel, Dustin M.; Salinas, Jose; Meyer, Andrew D. (Frontiers in Immunology, 2024)
Acute kidney injury (AKI) and multiple organ failure (MOF) are leading causes of mortality in trauma injuries. Early diagnosis of AKI and MOF is vital to improve outcomes, but current diagnostic criteria rely on laboratory markers that are delayed or unreliable. In this study, we investigated whether damage associated molecular patterns such as high mobility group box 1 (HMGB1), syndecan-1 (SDC-1) and C3a correlate with the development of trauma-induced AKI and MOF. Thirty-nine swine underwent smoke inhalation and severe burns, then received critical care for 72 hours or until death. AKI was defined by the KDIGO (Kidney Disease: Improving Global Outcomes) criteria, which labels AKI when a 1.5-fold increase in blood creatinine levels from baseline or a urine output < 0.5 mL/kg/h for 6 hours or more occurs. MOF was defined by the presence of both AKI and acute respiratory distress syndrome (PaO2/FiO2<300 for 4 hours). Results document that eight of 39 pigs developed AKI and seven of those developed MOF. Pathological analysis revealed that polytrauma induces significantly higher kidney injury scores compared to sham controls. The average time from injury to KDIGO AKI was 24 hours (interquartile range: 22.50-32.25). Twelve hours after injury, HMGB1 levels were significantly increased in animals that went on to develop AKI compared to those that did not (73.07 ± 18.66 ng/mL vs. 31.64 ± 4.15 ng/mL, p<0.01), as well as in animals that developed MOF compared to those that did not (81.52±19.68 ng/mL vs. 31.19 ± 3.972 ng/mL, p<0.05). SDC-1 and C3a levels were not significantly different at any time point between groups. ROC analysis revealed that HMGB1 levels at 12 hours post-injury were predictive of both AKI and MOF development (AKI: AUROC=0.81, cut-off value=36.41 ng/mL; MOF: AUROC=0.89, cut-off value=36.41 ng/mL). Spearman's correlation revealed that HMGB1 levels at 12 hours correlated with multiple parameters of AKI, including blood urea nitrogen, blood creatinine, and blood myoglobin. Our conclusion is that twelve-hour post-injury HMGB1 levels predict AKI and MOF in a smoke inhalation and burn swine model. Further research is needed to validate this result in other polytrauma models and in critical combat causalities.